Optimizing the halal food sector to support Indonesia as a leading global halal producer - Putri, Fitri Anisa Nusa; Rafiuddin, Muhammad (Journal of Halal Product and Research (JHPR), 2025)
Indonesia, as a country with the largest Muslim majority population in the world, can have great potential in increasing halal-based industries, especially in the food and beverage cluster. The growing trend of halal consumption confirms the Muslim community's growing awareness of Islamic principles and consideration of maqashid shariah. This study uses a method with a descriptive qualitative approach through library research in analyzing the optimization of halal food and beverage clusters to support Indonesia as a world halal producer. The results of this study found that the optimization of the halal food and beverage sector can be carried out by accelerating halal certification in the food and beverage industry, strengthening the halal value chain of food and beverage clusters, and strengthening the export-oriented halal food and beverage industry ecosystem. This research has limitations on the themes discussed and the literature used. The next research is expected to expand the discussion of the halal industry in Indonesia as a whole.   Keywords: Optimization, Halal Industry, Food, Beverages